Attitudes of Postgraduate Students Towards Distance Education During the COVID-19 Pandemic: North Cyprus Example - Aksoy, Yeşim Üstün (Frontiers in Psychology, 2021)
Distant education model has become the most common educational model worldwide due to the COVID-19 pandemic which emerged in China by the end of 2019. In North Cyprus (NC), traditionally face-to-face education had been resumed through online channels. The rapid shifting to online channels not only caused distress among the students who do not have experiences in online education system but also surfaced many problems for the access to the education. This study aims to lay out the attitudes and views of the higher education students in NC regarding the distant education during the COVID-19 pandemic in 2020-2021 educational year. In this quantitative study, scanning model is used. Random sample is used for the determination of the study group which was constructed with 470 volunteered higher education students. In terms of analysis of the data were collected from the students, it is determined that they received x ̅=82,52±19,50 points from the overall Attitudes Scale Regarding the Use of Distant Education Environments During the Pandemic (ASRUDEEDP), x ̅=23,03±7,21 points from competence and education sub-dimension, x ̅=26,36±5,81 points from practicality sub-dimension, x ̅=18,20±4,83 points from the efficiency sub-dimension and x ̅=14,93±4,12 points from the satisfaction sub-dimension. It is identified that the points do not indicate any difference according to the age group, grade and internet use durations (p>0,05) as the points of male students are observed as higher than of female when the points obtained in the sub-dimensions of competence and motivation as well as practicality within the ASRUDEEDP.